Penerapan Teknologi Perontok Debu Karpet Tempat Ibadah di Masjid Wilayah Desa Wonokerso, Kecamatan Pakisaji, Kab Malang - Yoto Yoto; Didik Nurhadi; Agus Suyetno; Putri Ardista Nursisda Mawangi; Muhammad Idris Effendi; Putrinda Inayatul Maula (I-Com: Indonesian Community Journal, 2025)
Carpet cleanliness in mosques remains a crucial issue at Mosque, Wonokerso Village, Pakisaji District, due to limited equipment and ineffective manual cleaning methods that pose health risks to volunteers. To address this, the community service team from Universitas Negeri Malang developed and implemented an appropriate technology-based carpet dust remover with a beater and vacuum system. The program involved problem identification, tool design and testing, user training, and performance evaluation. Function tests showed that the machine could clean up to 642.6 m² of carpet per hour, significantly more efficient than traditional methods. This initiative enhanced worship comfort, community participation, and partner self-reliance in managing mosque hygiene. The results highlight the importance of simple, applicable technological innovations to meet specific local needs and support sustainable cleanliness of religious facilities.